Didattiche innovative: il contributo delle pedagogie e delle discipline - Cappa, Carlo; Ghibaudi, Elena; Tovena, Francesca; Venanzi, Mariano (Chimica nella Scuola, 2023)
This contribution reports, in the form of an interview, the contents of a round table dedicated to the teaching innovation provided by the integration of pedagogical and disciplinary teachings. This round table has been held on 2022 in the framework of “Future Sight Tor Vergata”, a series of events promoted on occasion of the 40th anniversary of the University of Rome Tor Vergata (UTV).